PENGARUH ANGER MANAGEMENT TRAINING TERHADAP PENURUNAN PERILAKU AGRESI PADA SISWA BERMASALAH DI SMP X BANDUNG: he effect of Anger Management Training (AMT) to decrease agression behavior at junior high school “x” Bandung - Meilia Ishar (JURNAL PSYCHOMUTIARA, 2021)
Aggression is all form of behavior which meant, to hurt other individual physically and mentally or harm the others which their behavior is undesireable (Berkowitz 1995). Aggressive behavior is a form of negative behaviors that arise mainlydue to the stimulation of environmental stimuli often lead to greater impact. Aggression can be physical or verbal, and may occur on other people or objects that become targets of aggression. Aggressive behavior shown junior high school students 'X' Bandung include fights either alone or in groups, pushing, hitting, and kicking her or inventory such asschool desks, chairs and doors (Displacement) due to a simple problem. Students also like to taunt and threaten her friends who do not follow their will (bullying), students also often yell and say rude to her if what she wants is not obeyed. The purpose of the research was to obtain empirical data on the effect of Anger Management Training (AMT) to decrease agression behavior at junior high school “x” Bandung. This AMT is focusing to changing of behavior through increase knowledge, helping student to be able to control their temper positively and able to express anger in a healthy way. In this study there were fifteen participants taken as a subject by using purposive techniques based on established criteria.Todetermine whether there is the effect of the AMT in reducing aggressive behavior of students, the data processing is doneby using the Wilcoxon Signed Ranks test statistic test. Statistical hypothesis proposed in this study is : there is the effect of interventions such as anger management training to decrease aggressive behavior in the study subjects. : there is the effect of interventions such as anger management training to decrease aggressive behavior in the study subjects. From theresults of statistical tests using the Wilcoxon Signed Ranks Test results obtained Z value of -3.410 with probability p for atwo-tailed test (asymp. Sig. 2 tailed) of 0.001. Given the value of p = 0.001 <a = 0.05, then is rejected and is accepted. Thus, it can be said that there is the effect of interventions such as anger management training to decreaseaggressive behavior in students. Keywords: aggression, anger management training,